Lag Time of Pediatric Supra Tentorial Brain Tumors in Lower Middle Income Countries (LMIC) - Mehvish Zahra Alavi, Amber Goraya, Alia Ahmed, Tooba Mir, Romaisa Sheikh, Maham Ashraf, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The most common and frequent tumors in the children’s are central nervous system tumors (CNS). Objective: For evaluation of the lag time and clinical spectrum of pediatric supratentorial brain tumors from the time of appearance of symptoms in a patient to the time the patient presents to the hospital. Study design: It is an observational and cohort study conducted in the radiology and oncology department of our institute teaching hospital. Material and Methods: This prospective research was conducted at the oncology department of the children hospital ICH Lahore for one year. The study was approved by the IRB. The duration of the study was from March 2021 to March 2022. The sample size was calculated. The patients of age range between 0 months to 17 years were included in the study. SPSS version 24.0 was used for statistical analysis. Data will be stratified to see the effect modulators. Results: This study included 60 patients 30 girls and 30 boys. The average age of the patients at the time they were diagnosed with pediatric supratentorial brain tumor was 7 years. The majority of the patients reported to have type I neurofibromatosis. Some of the most common symptoms that the patients reported were vomiting, oculo-visual issues, motor problems, headache and endocrine dysfunction. Conclusion: The lag time and clinical spectrum of pediatric supratentorial brain tumors from the time of appearance of symptoms in a patient to the time the patient presents to the hospital was reported to be 2-6 months in majority almost 61% of the children. The 71% children visited the two regional area doctors before visiting the tertiary care hospital. The complex interplay of underdiagnoses, unavailability of the neuro-oncology treatments facilities and higher rates of abandonment in the LIMC are the basic reason behind survival gaps of the delayed presented patients. Keywords: Pediatric supratentorial brain tumors, lag time, low/middle income countries (LMIC), Central nervous system (CNS) tumors and intraxial tumors.